Coping strategies and social support in nursing students during clinical practice: A scoping review - Fernanda Loureiro; Dina Peças; Ana Cristina Neves; Ana Vanessa Antunes (Nursing Open, 2024)
Abstract Aim To identify the coping strategies and social support received by nursing students during clinical practice. Design Scoping review. Methods Primary studies on coping strategies and social support, in full text, in English, French, Spanish or Portuguese and published in 2018 or later were included. Search was carried out in January 2023 on EBSCOhost, PubMed, SciELO, ScienceDirect, OpenAIRE, MedNar Search, WorldWideScience and the references of previously selected articles. Results A total of 24 studies were identified. Seven studies mentioned social support as a useful strategy and several instruments were identified that allow measurement. Conclusions Few studies establish a direct relationship between the effectiveness of coping strategies with stressful situations. Positive coping strategies are associated with effective stress management. The relationship between social support and stress reduction is scarcely addressed. Implications for the Profession and/or Patient Care Stressful situations can have an impact on students' health and on the quality of care. Nursing schools and healthcare institutions must work together in programmes to improve students coping abilities. Impact This review addressed coping strategies used by nursing students during clinical practice. A set of relevant coping strategies were identified that can be used by teachers to improve students' outcomes. Reporting Method The review was performed according to Preferred Reporting Items for Scoping Reviews (PRISMA‐ScR). Patient or Public Contribution No patient or public contribution.